Łódzka Orkiestra Symfoniczna czasów Wielkiej Wojny w recenzjach Feliksa Halperna - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The Symphonic Orchestra in Lodz was established in 1915 and was the most important music-related undertaking in Lodz during the First World War. This team of musicians consisted of both professional musicians and novices. A lack of funds and instruments were major problems faced by the orchestra. Nevertheless, the music created by the SOL attracted numerous music aficionados living in Lodz, as well as well-known artists from outside the city, who were willing to create music together with the main line-up. Performances delivered by the musicians were also evaluated and analyzed by the local press. One of their most important detractors was Felix Halpern, who kept track of the concerts of the orchestra, as well as the various undertakings of its individual members. Reviews written by Halpern illuminate the music-related world of Lodz, focusing on the orchestra’s artists and audiences, evaluations and analyses of its performances in the press, and the individuals who co-financed the orchestra. These are extremely important for understanding the cultural life of Lodz during the aforementioned epoch.